Para Wali Nyentrik: Rekontekstualisasi Islamisasi di Tanah Jawa, Menantang Fundamentalisme Islam - Garadian, Endi Aulia (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
George Quinn, Bandit Saints of Java: How Java's eccentric saints are challenging fundamentalist Islam in modern Indonesia. Leicestershire: Monsoon Books Pte. Ltd.. 432 pp. Nowadays, religious fundamentalism is started to undermine the joints of diversity in Indonesia. For the extreme instance, adherents of this understanding even try to replace Pancasila as an ideology of Indonesia with Islamic state. The book is an oasis in the midst of the surge of fundamentalism. By contextualizing the stories of Islamization in Java through the bewildered journey of his pilgrimage to the tombs of the saints, he tried to present the trinkets of Islamic expression that developed in the stream of Indonesian history. This book also shows how the saints tried to “breakthrough” the solidity of Hindu-Buddhist civilization living as the mentality in Javanese people through unique Islamization tactics. The nuances of fusion between Islam and locality, as well as obedience to worship with magical power of syncretics meet in a historical continuity. In addition, the stories of the saints chosen by Quinn were able to show a model of Islamization that was friendly, fun, and flexible. This model, in turn, also gave birth to a genuine version of Islam in Indonesia.